Named Data Object Organization in Distributed Name Resolution System for Information Centric Network Environment - Hassan, Suhaidi; Elbreiki, Walid; Arlimatti, Shivaleela; Habbal, Adib (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
The Information-Centric Networking (ICN) is an emerging network communication model that focuses on what is being exchanged rather than who is exchanging information within a network. The named hosts make use of Named Data Objects (NDO) for data registration and name resolution. The Name Resolution System (NRS) is an element of the ICN that translates the object identifiers into network addresses. Distributing the NRS is an important and challenging issue for increased NDO registering, acquiring and storage. This study proposes a new NRS mechanism called the Distributed Name Resolution Mechanism (DNRM) to address the most significant issue of segregating the network and Balanced Binary Tree (BBT) structure to manage storage on the ever-increasing number of NDOs. The study formulates the proposed DNRM through the nearest neighbor algorithm by adding phases, means and methods, and probable outcomes. The stored NDOs are balanced with a balance factor to increase the scalability of NRS. The result shows that the overall NDO searching time is reduced by half for each iteration, and the proposed mechanisms are faster and more stable than the existing solutions in terms of better grouping NDOs. Both the mechanisms are simulated in the OMNeT++ simulation environment, a discrete event based simulator. The experimental results ensure that both the mechanisms have advantages in improving the network performance by minimizing the end-to-end delay and improving the network throughput.